Insights in the molecular mechanisms of an azole stress adapted laboratory-generated Aspergillus fumigatus strain. (7th February 2021) - Aruanno, Marion; Gozel, Samantha; Mouyna, Isabelle; Parker, Josie E; Bachmann, Daniel; Flamant, Patricia; Coste, Alix T; Sanglard, Dominique; Lamoth, Frederic
Abstract: Aspergillus fumigatus is the main cause of invasive aspergillosis, for which azole drugs are the first-line therapy. Emergence of pan-azole resistance among A. fumigatus is concerning and has been mainly attributed to mutations in the target gene ( cyp51A ). However, azole resistance may also result from other mutations ( hmg1, hapE ) or other adaptive mechanisms. We performed microevolution experiment exposing an A. fumigatus azole-susceptible strain (Ku80) to sub-minimal inhibitory concentration of voriconazole to analyze emergence of azole resistance. We obtained a strain with pan-azole resistance (Ku80R), which was partially reversible after drug relief, and without mutations in cyp51A, hmg1, and hapE . Transcriptomic analyses revealed overexpression of the transcription factor asg1, several ATP-binding cassette (ABC) and major facilitator superfamily transporters and genes of the ergosterol biosynthesis pathway in Ku80R. Sterol analysis showed a significant decrease of the ergosterol mass under voriconazole exposure in Ku80, but not in Ku80R. However, the proportion of the sterol compounds was similar between both strains. To further assess the role of transporters, we used the ABC transporter inhibitor milbemycine oxime (MLB). MLB inhibited transporter activity in both Ku80 and Ku80R and demonstrated some potentiating effect on azole activity. Criteria for synergism were reached for MLB and posaconazole against Ku80. Finally, deletion of asg1 revealed some role of this transcription factor in controlling drug transporter expression, but had no impact on azole susceptibility. This work provides further insight in mechanisms of azole stress adaptation and suggests that drug transporters inhibition may represent a novel therapeutic target. Lay Summary: A pan-azole-resistant strain was generated in vitro, in which drug transporter overexpression was a major trait. Analyses suggested a role of the transporter inhibitor milbemycin oxime in inhibiting drug transporters and potentiating azole activity.